Formulation and In Vitro - In Vivo Evaluation of Quercetin Loaded Eudragit S100 Microspheres - Jat, Ramchandra (Asian Journal of Pharmaceutics (AJP), 2018)
Background: Sulfur mustard (SM), well known as the mustard gas, when contacts the skin can cause stern blisters and causes systemic toxicity as well, affects eyes, skin, and respiratory tract. Till now, exact therapy to counteract SM-induced systemic toxicity has not been developed yet. SM-induced toxicity can be reduced by cellular glutathione replenishment. Plant flavonoids, for example, quercetin and gossypin possess antioxidant, radical scavenging activity. Employing this attribute, quercetin-loaded Eudragit microspheres were fabricated to enhance the oral bioavailability of the quercetin. Materials and Methods: Drug-loaded microspheres were prepared using emulsion-solvent diffusion method. Results and Discussion: Particles so obtained were within the micrometer range (48.25 ± 2.01–100.40 ± 3.01 μm for QM1 to QM10 batches). Fourier transform infrared spectra indicated no drug-polymer interaction whereas differential scanning calorimetry thermograms revealed the absence of crystalline drug in the drug-loaded microsphere formulation. Scanning electron micrographs showed that the fabricated microspheres were spherical in shape. Batch QM3 displayed 73% encapsulation efficiency with highest in vitro drug release rate (98%). Bioavailability studies showed that quercetin loaded Eudragit S100 microspheres were able to enhance the oral bioavailability of the drug. As per stability studies, the developed formulation was stable when tested under accelerated stability conditions. Conclusion: The fabricated quercetin-loaded Eudragit S100 microspheres were able to enhance the bioavailability of the drug in the serum of the animal model.